2015
DOI: 10.18632/oncotarget.6393
|View full text |Cite
|
Sign up to set email alerts
|

Lack of survival advantage with autologous stem-cell transplantation in high-risk neuroblastoma consolidated by anti-GD2 immunotherapy and isotretinoin

Abstract: Since 2003, high-risk neuroblastoma (HR-NB) patients at our center received anti-GD2 antibody 3F8/GM-CSF + isotretinoin – but not myeloablative therapy with autologous stem-cell transplantation (ASCT). Post-ASCT patients referred from elsewhere also received 3F8/GM-CSF + isotretinoin. We therefore accrued a study population of two groups treated during the same period and whose consolidative therapy, aside from ASCT, was identical. We analyzed patients enrolled in 1st complete/very good partial remission (CR/V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 53 publications
5
65
1
3
Order By: Relevance
“…A likely reason for this transient decline in tandem transplants for neuroblastoma could be due to the increased use of immune based therapies such as anti-GD2 antibodies. 21 This decline will need to be evaluated in future observations, since the most recent randomized controlled trial conducted by the Children's Oncology Group demonstrated an improved event free survival with tandem transplants for neuroblastoma. 22 Tandem transplants are increasing for CNS tumors, consistent with data that has shown improved survival with this approach.…”
Section: Discussionmentioning
confidence: 99%
“…A likely reason for this transient decline in tandem transplants for neuroblastoma could be due to the increased use of immune based therapies such as anti-GD2 antibodies. 21 This decline will need to be evaluated in future observations, since the most recent randomized controlled trial conducted by the Children's Oncology Group demonstrated an improved event free survival with tandem transplants for neuroblastoma. 22 Tandem transplants are increasing for CNS tumors, consistent with data that has shown improved survival with this approach.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective non-randomized study of historical results at a single institution with extended follow-up, patients with high-risk neuroblastoma treated with or without myeloablative therapy had similar survival rates. Therefore, the authors concluded that courses of myeloablative therapy may not be needed to improve outcome when anti-GD2 immunotherapy is used for consolidation after dose-intensive conventional chemotherapy [85]. These mixed results suggest that the optimal consolidation regimen for patients with highrisk neuroblastoma remains to be determined, likely through carefully controlled, large-scale international clinical trials.…”
Section: Consolidationmentioning
confidence: 99%
“…Our results suggest markedly worse survival in this setting compared with high‐risk pediatric neuroblastoma patients in North America, Europe, and Asia. Specifically, five‐yr overall survival in our setting was 24% (95% CL: 10%, 41), whereas the highest reported five‐yr overall survival in North America was 76% (95% CL: 66%, 88%) in a highly select group of high‐risk pediatric neuroblastoma patients . In addition, our review of prior studies suggests considerable variation in survival even between developed countries.…”
Section: Discussionmentioning
confidence: 59%
“…Table describes 13 published reports , and the current study, of five‐yr overall survival among high‐risk pediatric neuroblastoma and summarizes survival differences compared with our population. Half of the reports pertained to high‐risk pediatric neuroblastoma cohorts in North America.…”
Section: Resultsmentioning
confidence: 99%